Manures Effectivity to Enhanced the Availability of Phosphorus, Crops Growth and Yield of Rice and Corn in Acid Upland Soil - Yoyo Sulaiman (JOURNAL OF TROPICAL SOILS, 2008)
The research was conducted in Tamanbogo Station Research in the 2007 Rainy Season in upland rice-corn intercropping farming. The research design used Randomized Complete Block Design with 3 replications. The treatments were 1). 15 t ha-1 manures + Residues of rock phosphate (RRP),  2). Without manures + RRP, 3). 15 t ha-1 manures + 150 kg  ha-1 SP 36 and  4). Without manures + 150 kg ha-1 SP 36. The upland rice was seeded in planting space of 25 cm x 25 cm, 2-3 seeds/hill. The land was treated with 1 t ha-1 of RP in the last farming year while SP36 was applicated each season. Urea and KCl fertilizers that were used on upland rice were 300 kg ha-1 and 100 kg ha-1, respectively while corns were fertilized with 250 kg ha-1 urea and 100 kg KCl ha-1. The research results showed that the availability of N and K nutrients in the soil at the time of before planting was low but the availability P was high. Application of manures and RRP increased C-organic, availability of P , Ca and  Cation Exchangeable Capacity in the soil. Application of 15 t ha-1 of manures with RRP increased dry biomass weight of rice and corn, there were 45.17 % and 49.23 %, respectively. The grain yield of rice and corn on the treatment of manures and RRP were not gave significant different compare to the yield was gained with SP 36  fertilizer.